2020
DOI: 10.1155/2020/8823877
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Venetoclax and Dexamethasone in Refractory IgM Primary Plasma Cell Leukemia with t(11;14) and TP53 Mutation: A Case Report and Literature Review

Abstract: Primary plasma cell leukemia (pPCL) is an uncommon disease. IgM multiple myeloma (MM) is an infrequent subtype that accounts for less than 1 percent of MM cases. IgM pPCL is quite rare with only a few cases published to date. We describe a case of a patient with IgM pPCL who initially presented with hyperviscosity syndrome requiring urgent plasma exchange. His bone marrow biopsy demonstrated t(11;14). He progressed on proteasome inhibitors, immunomodulating agents, and other chemotherapy medications but later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…[10][11][12] Several published case reports have supported the use of venetoclax as a treatment agent for PCL as monotherapy or as part of a combination regimen. [13][14][15][16][17][18][19] The following case reinforces the effectiveness of venetoclax use in the setting of PCL, but additionally illustrates its potential to induce complete remission as a bridge toward consolidation with autologous SCT.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…[10][11][12] Several published case reports have supported the use of venetoclax as a treatment agent for PCL as monotherapy or as part of a combination regimen. [13][14][15][16][17][18][19] The following case reinforces the effectiveness of venetoclax use in the setting of PCL, but additionally illustrates its potential to induce complete remission as a bridge toward consolidation with autologous SCT.…”
Section: Introductionsupporting
confidence: 58%
“…The t (11;14) translocation is a cytogenetic abnormality that occurs more frequently in PCL than in MM and may serve as a predictive biomarker for venetoclax. 16 Findings from the BELLINI trial suggested that patients with t (11;14) and high BCL2 expression have a favorable outcome with venetoclax, further highlighting that biomarker-driven treatment strategies is a possible approach for t(11;14) PCL patients. Although the mechanism of venetoclax has not been fully elucidated, it is thought that high expression of BCL-2 plays a pivotal role in tumor growth and survival, making venetoclax's unique mechanism in targeting this intrinsic apoptotic pathway a favorable therapy option.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite possessing the hallmarks of terminally differentiated PCs, venetoclax sensitive MMs retain or aberrantly reactivate aspects of the B-cell program, including BCL2 dependence, along with other specific patterns of B-cell gene expression and chromatin accessibility, and point to novel biomarkers of venetoclax sensitive MM independent of t(11;14) [ 19 ]. Currently, there are very little data from case reports on the efficacy of venetoclax in pPCL with t(11;14) [ 26 , 35 , 36 , 37 ], and defining a specific predictor of venetoclax sensitivity is challenging. Our study focused on the expression levels of the BCL2 gene family and of a panel of B-cell genes associated with venetoclax sensitive MM [ 19 ] in both MMs and pPCLs stratified for the presence of t(11;14).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective “real world” datasets also support the efficacy of venetoclax in t(11;14) positive myeloma, with frequent responses (> 90%) and a median PFS of 10 months among patients with R/R disease in one series [ 127 ]. Responses have also been observed among patients with plasma cell leukemia, in which t(11;14) is frequently detectable, and future studies are required to further evaluate the role of BCL2 inhibition is this high-risk disease [ 127 129 ].…”
Section: Efficacy Of Venetoclax In Other B Cell Neoplasmsmentioning
confidence: 99%